MENGELOLA ADMINITRASI PERGUDANGAN DI DALAM PELABUHAN TANJUNG PRIOK - Rizky Yudi Prasetyo; Muhammad Rangga Hidayat; Arif Rachman Dillah; Siti Sahara (Jurnal Ilmiah Wahana Pendidikan, 2023)
Warehousing administration is a management process that involves managing, supervising, and organizing all activities related to warehousing. The main goal of warehousing administration is to optimize the use of available resources and ensure operational efficiency of the warehousing. Warehousing administration includes several tasks, such as planning, inventory control, stock management, shipping, receiving, and data management. The warehousing administration process can help companies to reduce costs and increase profits by optimizing the warehousing process and minimizing errors or losses. In the digital era, warehousing administration is increasingly using information technology to improve efficiency and accuracy in managing warehousing data. Overall, warehousing administration is important to ensure warehousing operations run smoothly and efficiently.